The role of knowledge artefact and agency in IS project escalation - Bukhary, Wael (2014)
This research contributes to current academic thinking by highlighting new perspective to studying the IS Project Escalation phenomenon through the application of Agency Theory. This theory views the customer as the (principal) who needs an IS product, and the IS developer as the (agent) who creates this IS product. According to this viewpoint, examining current IS project escalation literature suggests the majority of previous studies implicitly adopted the assumption that the customer (principal) is entirely capable of identifying the requirements of the proposed IS product, and a project is prone to escalate because of the attitude of the IS developer (agent). This presents a gap in the literature in that the impact of the customer (principal) not been explicitly explored. As such, one critical aim of this research is to investigate IS project escalation by employing an extension of Agency Theory. This extended theory assumes that the customer (principal) suffers challenges of incompetence when it comes to the transfer of knowledge (i.e. requirements) to the IS developer (agent). This leads to a situation of information asymmetry on the principal’s side because of incomplete knowledge transfer. In turn, this situation develops and leads to IS project escalation. Another aim of this research is to investigate the process of requirement elicitation (RE) in IS development practice. This is to identify the role of the incorporated knowledge artefacts within this activity, in terms of how the project manager and developers effectively create and utilise these objects. Thus, this is in order to provide a possible solution with respect to the challenge of incomplete knowledge transfer.